2010
DOI: 10.1002/app.31145
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of aramid fibers under alkaline and neutral conditions: Relations between the chemical characteristics and mechanical properties

Abstract: Aramid fibers are high-performance materials that have been used in various applications such as heat and cut protection, composites, rubber reinforcement, ropes and cables, and fabrics; today their use is proposed in geotextiles for alkaline ground reinforcement, and they have been used in cables for marine applications for a few years. However, there is a lack of experience with the long-term behavior of aramid fibers in wet and alkaline environments. Aging studies were therefore performed on Twaron 1000 fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
1
11
0
3
Order By: Relevance
“…The corresponding chromatograms are shown in Figure 10. The M w evolutions are consistent with the viscosity measurements from a previous study [21]. The degradation is significantly higher at pH11 than at pH9.…”
Section: Mass Distribution Evolutionsupporting
confidence: 90%
See 2 more Smart Citations
“…The corresponding chromatograms are shown in Figure 10. The M w evolutions are consistent with the viscosity measurements from a previous study [21]. The degradation is significantly higher at pH11 than at pH9.…”
Section: Mass Distribution Evolutionsupporting
confidence: 90%
“…A previous study has shown that in moderate alkaline environments (pH9 and pH11) the chemical degradation of Twaron 1000 fibres can be fitted by Springer et al's equation 1, using one decay function at pH9 and two decay functions at pH11 [21]. We assumed thus that the degradation may be attributed to one degradation process at pH9 and two degradation processes at pH11.…”
Section: Mass Distribution Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…After extraction of the finish with deionised water at ambient temperature, FTIR analyses of the isolated finish enable the peak located at w2923 cm À1 to be attributed to the finish. As Technora fibres contain PPTA sequences similar to Twaron fibres, the spectra display some peaks related to the amide functions in common [10]: the peak located at w1639 cm À1 is related to the C]O vibration and the peak at w1306 cm À1 is related to the C-N, N-H and C-C combined vibrations. The peaks related to the amide functions of PPTA and 3-4 0 -POP-T sequences are not clearly separated.…”
Section: Evaluation Of the Surface Degradation: Ftir-atrmentioning
confidence: 99%
“…Styrene cured unsaturated polyesters are, by far, the most important composite matrices undergoing hydrolysis. Among other polymers in which problems of hydrolytic ageing have been observed, one can cite: polyamides, including aromatic ones (for instance, Kevlar) [122], anhydride cured epoxies, polyurethanes based on polyesters, vinyl esters, polyvinyl acetate used as low profile additive in polyester sheet molding compounds or bulk molding compounds, etc. There is not, to our knowledge a theoretical tool able to predict the hydrolysis rate of a given group in a given polymer.…”
Section: Effect Of Structurementioning
confidence: 99%